Perilaku primata monyet ekor panjang (Macaca fascicularis) di Kebun Binatang Surabaya (KBS) - Arianti, Okta Fina; Salsabila, Nurizza (Filogeni: Jurnal Mahasiswa Biologi, 2024)
Kebun Binatang Surabaya (KBS) as a primary conservation area. The zoo is useful for efforts in the care and breeding of various species. The long-tailed macaque (Macaca fascicularis) is one of the primates with a wide distribution, spanning Southeast Asia. Studying the daily behavior of long-tailed macaques at Kebun Binatang Surabaya is important to understand their habits. The type of research conducted in this study is observational. The method used for recording the daily behavior of long-tailed macaques is focal time sampling. The research subjects include one adult male, one adult female, and one juvenile male. The results showed that the juvenile male long-tailed macaque (M. fascicularis) had the most activities with a total of 2,107 activities, while the adult male had the fewest with a total of 1,876 activities. There are 9 activities observed in the long-tailed macaque (M. fascicularis), which include mating, sleeping, agonistic behavior, playing, vocalizing, grooming, inactivity, eating, and moving.